Nursing implications: symptom presentation and quality of life in rectal cancer patients. Issue 9 (16th March 2016) - O'Gorman, Claire; Barry, Amanda; Denieffe, Suzanne; Sasiadek, Wojciech; Gooney, Martina
Abstract : Aims and objectives: To determine the changes in symptoms experienced by rectal cancer patients during preoperative chemoradiotherapy, with a specific focus on fatigue and to explore how symptoms impact the quality of life. Background: Rectal cancer continues to be a healthcare issue internationally, despite advances in management strategies, which includes the administration of preoperative chemoradiotherapy to improve locoregional control. It is known that this treatment may cause adverse effects; however, there is a paucity of literature that specifically examines fatigue, symptoms and quality of life in this patient cohort. Design: A prospective, quantitative correlational design using purposive sampling was adopted. Methods: Symptoms and quality of life were measured with validated questionnaires in 35 patients at four time points. Results: Symptoms that changed significantly over time as examined usingrm‐anova include fatigue, bowel function issues, nutritional issues, pain, dermatological issues and urinary function issues. Findings indicate that fatigue leads to poorer quality of life, with constipation, bloating, stool frequency, appetite loss, weight worry, nausea and vomiting, dry mouth and pain also identified as influencing factors on quality of life. Conclusion: Findings have highlighted the importance of thorough symptom assessment and management of patients receiving preoperative chemoradiotherapy, particularly midway through treatment, in order to optimise quality of life and minimise interruptions to treatment. Relevance to Clinical Practice: Close monitoring of symptoms during preoperative chemoradiotherapy, particularly at week 4, will enable the implementation of timely interventions so that interruptions to treatment are prevented and the quality of life is optimised, which may hasten postoperative recovery times.